1999
DOI: 10.1038/sj.onc.1202979
|View full text |Cite
|
Sign up to set email alerts
|

The fibroblast growth factor receptor FGFR-4 acts as a ligand dependent modulator of erythroid cell proliferation

Abstract: Receptor and non-receptor tyrosine kinases constitute a large family of proteins that play a pivotal role in hematopoiesis. Here we conducted a comprehensive survey of tyrosine kinase gene expression in primary erythroid progenitor cells from bone marrow by employing a PCR-based strategy that targets the conserved kinase encoding region. We demonstrate that erythroid progenitor cells express several receptor and nonreceptor tyrosine kinases, like c-kit, Jak1, Ryk, FAK, Syk, Arg, Csk and members of the insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…bFGF was however reported to be important for proliferation of hemangioblast, a common progenitor of endothelial and hematopoietic cells (Faloon et al, 2000). Additionally, bFGF was found in our previous studies to synergize with other growth factors in inducing proliferation of primitive uncommitted progenitors and de®nitive erythroid cells (Koritschoner et al, 1999). We demonstrate here that bFGF is a key factor for proliferation and survival of primitive erythroid progenitors and thus in fact represents a hematopoietic growth factor.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…bFGF was however reported to be important for proliferation of hemangioblast, a common progenitor of endothelial and hematopoietic cells (Faloon et al, 2000). Additionally, bFGF was found in our previous studies to synergize with other growth factors in inducing proliferation of primitive uncommitted progenitors and de®nitive erythroid cells (Koritschoner et al, 1999). We demonstrate here that bFGF is a key factor for proliferation and survival of primitive erythroid progenitors and thus in fact represents a hematopoietic growth factor.…”
Section: Discussionmentioning
confidence: 58%
“…Our previous work demonstrated that bFGF cooperates with various growth factors in the development of de®nitive erythroid progenitor cells (Koritschoner et al, 1999). Additionally, bFGF alone was found to be ine ective in supporting progenitor cell growth but caused sustained growth of immature progenitors derived from blastoderm that expressed elevated levels of v-Myb (Kara®at et al, 2001).…”
Section: Bfgf Causes Growth Of Primitive Erythroid Cells Containing Vmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of FGFR4 in carcinogenesis is poorly understood. FGFR4 mediates membrane ruffling in breast carcinoma cells (9), where it is overexpressed (10), and it has been shown to modulate erythroid cell proliferation (11). A tumor-derived FGFR4 (ptd-FGFR4) isoform recapitulates pituitary tumorigenesis in transgenic mice (12).…”
Section: Introductionmentioning
confidence: 99%